Controllable Synthesis of Web‐Footed PdCu Nanosheets and Their Electrocatalytic Applications. Issue 14 (12th February 2022) - Zeng, Tiantian; Meng, Xiaomin; Huang, Haowei; Zheng, Linwei; Chen, Haibo; Zhang, Yun; Yuan, Weiyong; Zhang, Lian Ying
Abstract: Morphological control of noble‐metal‐based nanocrystals has attracted enormous attention because their catalytic behaviors can be optimized well by adjusting the size and shape. Herein, the controllable synthesis of web‐footed PdCu nanosheets via a facile surfactant‐free method is reported. It is discovered that the Cu(II) precursor in this synthetic system displays a critical role in growing branches along the lateral of nanosheets. This work demonstrates a Pd‐based alloy nanoarchitecture for efficient and stable electrocatalysis of both ethanal and formic acid oxidation reactions. Abstract : The facile solution synthesis of web‐footed PdCu nanosheets as an efficient and stable electrocatalyst is demonstrated for electrooxidation of ethanal and formic acid. It is discovered that the Cu(II) precursor in this synthetic system displays a critical role in growing branches along the lateral of nanosheets. Control experiments show that the improvement originates from the combined electronic and structural effects.